Tanda-Tanda Akhir Zaman: Kristus Hadir - Jefri Feoh; Aprianus L Moimau (Jurnal Silih Asah, 2024)
The Bible clearly outlines various signs that will precede the second coming of Jesus Christ at the end of the age. These signs, such as wars, natural disasters, the rise of false prophets, and cosmic phenomena, are believed to be indicators that the present age is nearing its end and will be replaced by a new reality under the reign of Christ. As global conflicts, economic crises, and intensifying natural calamities unfold, many observers interpret these events as signs that Christ's return is imminent. While the exact timing remains unknown, Christians are urged to remain vigilant and fully prepare themselves spiritually and physically. Christ's glorious return will usher in the resurrection of the dead believers, the transformation of the universe, and the final judgment. For believers, this event marks the culmination of salvation and the fulfillment of the promise of eternal life in Christ's Kingdom.